Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Geometri Pada Siswa Kelas XI MIA 3 Semester Genap SMA Negeri 1 Tigapanah Tahun 2017/2018 - P., Vina Meliyana; Tobing, Grace Susanti (Jurnal Pendidikan Matematika dan Sains, 2017)
The purpose of this study was to determine the types of errors and factors that cause students to make mistakes in solving problems, namely in the understanding of the concepts of geometry, geometrical reasoning, and problem solving of geometry skills with geometry. This study uses a qualitative approach and the type of research carried out is descriptive, where to answer the problems used information from student worksheets collected through giving a number of questions as many as 4 questions to students with a duration of 30 minutes. The subjects of this study were 23 students of SMA XI IPA 3. The results showed that students were still weak in their ability to think geometry in visualization, analysis, and abstraction.